Intestinal prolape of an omphalo-mesenteric fistula - Bénié Adoubs Célestin; Kpangni Ahua Jean Bertrand; Lohourou Grah Franck; Traoré Ibrahim; Bony Ursula Constance; Traoré Abdoul Massandjé Nora; Nandiolo Koné Rose (Elsevier, 2022)
Intestinal prolapse through a persistence of the omphalo-mesenteric duct or vitelline duct is a very rare clinical entity. It is a complication of the omphalo-mesenteric fistula which requires emergency surgery. The authors report a case emphasizing the clinical and therapeutic aspects.